Pengaruh gender dan religiusitas terhadap etika penggelapan pajak - Widodo, Cinthiya Auliya Husna (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The largest source of state revenue or income among taxes, grants and non-taxes is taxes. Lack of awareness, public literacy as taxpayers and attitudes that do not care about the importance of the role of taxes can lead to tax avoidance attitudes that allow fraudulent practices in the tax system. So that the income obtained by the state from taxes in practice is often distorted or misused by irresponsible persons, the way is by tax evasion. This study examines whether gender and religiosity influence the ethics of tax evasion. In this study the authors used a descriptive verification method with a quantitative approach. Gender variable uses a dummy variable, Religiosity and tax evasion ethics use a Likert scale. The population used in this study is the Secretariat Taxpayer of Garut district. Simple random sampling is the sample technique used in this study, using primary data, namely distributing questionnaires and 70 respondents as samples in this study. Data were analyzed assisted by SPSS software. The research results obtained, namely gender has no effect on the ethics of tax evasion and religiosity has an effect on the ethics of tax evasion.